Surgical Team Compliance with the Surgical Safety Checklist in the Central Operating Theater: A Cross-Sectional Study - Widigdo Rekso Negoro; Agus Budi Prasetyo; Ircham Saifudin; Reko Priyonggo; Muhammad Rodli; Annes Rindy Permana (Jurnal Keperawatan Profesional, 2026)
Surgical procedures are high-risk interventions that require consistent implementation of the SSC to reduce preventable adverse events. However, differences in workflow and clinical urgency between elective and emergency procedures may influence surgical team compliance with SSC implementation. This study aimed to analyze the relationship between the type of surgical procedure and surgical team compliance with the SSC in the COT of a maternal and child hospital. A non-experimental observational study with a cross-sectional design was conducted involving 65 surgical procedures selected through accidental sampling from a population of 148 procedures. Data were collected through direct observation of SSC implementation during the sign-in, time-out, and sign-out phases and analyzed using the chi-square test. Most observed procedures were elective surgeries (55.4%). SSC compliance was achieved in 52.3% of procedures during the Sign-in phase, 67.7% during the time-out phase, and 72.3% during the sign-out phase. A statistically significant association was identified between the type of surgical procedure and SSC compliance (p=0.006). these findings support the need to strengthen SSC implementation through regular compliance audits, continuous surgical team training, and reinforcement of patient safety culture. Because of the cross-sectional design, the findings indicate an association rather than a causal relationship.